OPTIMIZATION OF HYDRAULIC FRACTURING DESIGN “KL-01” WELL “KALA” FIELD - Karina Larasati; Dimas Suryo Wicaksono; Rahajeng Suryo Rahmadhini; Ristiyan Ragil Putradianto; Achmad Helmi (Petro : Jurnal Ilmiah Teknik Perminyakan, 2026)
Well KL-01 in KALA Field was hydraulically fractured to increase the productivity of a well in a low permeability reservoir. The first treatment exhibited a large increase in production potential; nevertheless, the resulting fracture geometry was not totally ideal, due to the poor proppant placement and unequal distribution of fracture conductivity along the fracture. The study is aimed to analyze the fracture geometry, proppant distribution, fracture conductivity and production performance to assess the original hydraulic fracturing treatment and to identify an optimum redesign scenario. The study employed well log interpretation, reservoir characteristics, production data, step rate test, micro frac test, treatment program and post-job report. A pseudo-three-dimensional hydraulic fracturing model was used to predict fracture propagation, propped fracture length, fracture breadth, proppant placement, retained permeability, fracture conductivity, and dimensionless fracture conductivity. The base case model was validated with field test data and post job report. Sensitivity analysis of injection rate, proppant type, proppant size, pad volume and maximum proppant concentration was conducted afterwards. The first treatment enhanced the ratio of the productivity index by 3.42 and increased the output potential from 82.14 BLPD (3.94 BOPD) to 2061.78 BLPD (98.97 BOPD). For Well KL-01 with reservoir permeability of 4 mD, the best redesign was reached using low density ceramic proppant Carbolite 16/20 and increasing pad volume from 10,500 gallons to 18,000 gallons. The new scenario shows an increase in fracture conductivity from 4245.81 mD-ft to 7587.06 mD-ft and retained permeability rose from 250,984 mD to 551,786 mD. Thus, the enhanced hydraulic fracturing design leads to a better fracture geometry, more uniform proppant distribution, higher fracture conductivity and better production potential.